2009
DOI: 10.4149/neo_2009_04_303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dihydropyrimidine dehydrogenase gene (DPYD) coding sequence variants on the development of fluoropyrimidine-related toxicity in patients with high-grade toxicity and patients with excellent tolerance of fluoropyrimidine-based chemotherapy

Abstract: Alterations in dihydropyrimidine dehydrogenase gene (DPYD) coding for the key enzyme (DPD) of fluoropyrimidines (FPs) catabolism contribute to the development of serious FPs-related toxicity. We performed mutation analysis of DPYD based on cDNA sequencing in 76 predominantly colorectal cancer patients treated by FPs with early development of high (grade 3-4) hematological and/or gastrointestinal toxicity. Six previously described [85T>C (C29R), 496A>G (M166V), 775A>G (K259E), 1601G>A (S534N), 1627A>G (I543V), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
7
54
1
Order By: Relevance
“…Three additional clinical association studies failed to establish any link between M166V and 5-FU-related toxicities (4, 11, 28). A fourth study suggested that M166V may protect against hematological toxicity and neutropenia following administration of 5-FU; however, the association was observed only in women (12). The P1023T variant is rare in European populations and is more common in individuals of African ancestry (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three additional clinical association studies failed to establish any link between M166V and 5-FU-related toxicities (4, 11, 28). A fourth study suggested that M166V may protect against hematological toxicity and neutropenia following administration of 5-FU; however, the association was observed only in women (12). The P1023T variant is rare in European populations and is more common in individuals of African ancestry (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the M166V variant was shown to strongly associate with grade III and IV toxicity in a cohort of patients with breast, gastroesophageal, or colorectal cancer treated with 5-FU-based therapy (10); however additional reports failed to confirm a link between the variant and 5-FU toxicity (4, 11). Further studies have suggested that M166V might be protective against specific 5-FU-related toxicities in women (12). …”
Section: Introductionmentioning
confidence: 99%
“…The c.1129-5923C/G mutation in intron 10 created a cryptic splice donor site and as a consequence, a 44 bp fragment of intron 10 was inserted in the mature DPD mRNA, reducing its activity. Really, conflicting data exist as to weather the c.1236G/A mutation is associated with an increased risk of development of severe 5-FU-associated toxicity [75,80], because of its apparently high mutation prevalence in the normal population. These data refer the necessity to confirm the genetic screening for this mutation in cancer patients prior to the start of 5-FU-containing chemotherapy…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 97%
“…On this basis, subsequently, various strategies have been proposed to screen for patients with a DPD deficiency, including genotyping [74,75]. The evidence that DPYD heliotype not containing any no synonymous or splice-site mutations was associated with 5-FU toxicity suggested the presence of additional genetic variations in the nonbonding region of DPYD [74].…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 98%
“…86,87 Deenen et al found that 100% of patients carrying the IVS14+1 polymorphism developed severe toxicity. 88 Measuring DPYD activity has been suggested to be a better biomarker for fluoropyrimidine-induced toxicity than DPYD genotyping, although recent findings confirm that genotyping and haplotyping could be acceptable options for stratifying patients according to risk of toxicity 89 or establishing dose recommendations for capecitabine and as shown by the Pharmacogenetics Working Group of the Royal Dutch Pharmacists Association. 90 …”
mentioning
confidence: 99%